Pharmacoeconomic analysis of the use of tocilizumab in therapy for rheumatoid arthritis:imitation simulation - Dmitry Vladimirovich Goryachev; Sh F Erdes; E L Nasonov (Научно-практическая ревматология, 2010)
Heavy economic expenses for treatment with genetic engineering biologicals (GEB) in patients with rheumatoid arthritis (RA) determine what strategies are most optimal in terms of both their clinical efficiency and economic constituent should be sought for. Objective: To define the most optimal strategies to use tocilizumab and TNF-α inhibitors in a Russian population of patients with different duration of RA. Material and methods. The investigation was based on the cost-benefit analysis using imitation simulation. Modeling relied on the relationship of RA mortality to a patient's functional status rated by the health assessment questionnaire (HAQ). A model was constructed, which simulated the progression of functional incompetence in RA patients seeking medical advice in health care facilities of Russia. Five variants of the model were developed to simulate the sequence of changing the basic anti-inflammatory drugs (BAIDs), including the incorporation of tocilizumab or a TNF-α inhibitor. The first strategy that ignored the use of BAIDs involved palliative therapy alone, by simulating a gradual disease progression, and that was used to obtain data for comparison of results (reference). The second strategy estimated the sequence of BAID changes in the following order: methotrexate (MT) → leflunomide (LF) → sulfasalazine (SS) → azathioprine → palliative therapy. This strategy was also considered to obtain data for comparison of results. The third strategy comprised the use of tocilizumab or a TNF-α inhibitor after determining the resistance or intolerance of MT therapy. The fourth strategy assumed the use of tocilizumab or a TNF-α inhibitor after determining the resistance or intolerance of MT and LF therapy. The fifth strategy envisaged the use of tocilizumab or a TNF-α inhibitor after determining the resistance or intolerance of MT, LF, and SS therapy. The possibility that a combination of BAIDs and MT might be used and the impact of RA duration on lower HAQ scores were taken into account. Direct and indirect costs were calculated in terms of social aspects, their relationship to HAQ scores being derived. The cost of TNF-α inhibitors was taken as that of adalimumab. The model simulated the participation of 10,000 patients in each sequences. The prediction horizon was 10 years. The age of patients and the initial distribution of HAQ scores were taken from the results of the RAISER epidemiological survey. Results. The least additional cost per quality-adjusted life year (QALY) was when GEB was used after 3 synthetic BAIDs, no significant difference being found in the cost of tocilizumab and that of a TNF-αinhibitor. The additional cost for a TNF-α inhibitor used after 3 BAIDs in relatively early RA was about 500,000 rubles; that for tocilizumab was slightly higher - 560,000 rubles. The cost increased with the duration of RA and when the moment of using GEB approached that of discontinuation of the first synthetic BAID - MT. The administration of tocilizumab after MT turned out to be cost-effective in patients with relatively late RA - the cost per QALY was 845,000. The use of synthetic BAIDS was in terms of cost-based effectiveness was most optimal - about 40,000 rubles per QALY. The availability of additional agents permits the choice of the most optimal strategy for the use of GEB. Conclusion. The application of the imitation simulation technique demonstrated that the strategy of using GEB after several synthetic BAIDs in patients with the least duration of the disease is most optimal in the context of cost-based efficiency. In this regard, no great difference was found in the use of tocilizumab or TNF-α inhibitors